Estudo bioquímico, imunológico e farmacológico do veneno do escorpião Hadruroides lunatus e da patofisiologia do seu envenenamento - Fernanda Costal Oliveira (2013)
Hadruroides lunatus scorpions are the most abundant in the Peruvian central coast, where occurs most of the cases of stings and envenoming in humans. However, little is known about the composition and mechanism of action of venom. The aim of this study is to describe, in general terms, the biochemical, immunological and pharmacological characterization of H. lunatus venom as well as to analyze the pathophysiology of its envenoming. Proteomic analysis showed that H. lunatus venom is composed of peptides and proteins with molecular weights ranging from less than 2,000 Da to greater than 70,000 Da. The median lethal dose (LD50) via intracranial (i.c.) and intraperitoneal (i.p.) in mice were determined as 0.1 mg/kg to 21.55 mg/kg, respectively. As biochemical parameters it were evaluated hyaluronidasic, proteolytic and phospholipasic activities. Regarding immunological studies, we demonstrated cross-reactivity between H. lunatus venom and Tityus serrulatus and Centruroides sculpturatus venoms. Hematological analysis in envenomed rats showed that there was a significant decrease of leukocytes, neutrophils, eosinophils and lymphocytes in these animals. Furthermore, an increase was detected in serum total proteins, albumin and acute phase proteins, as well as CK, CK-MB, AST and LDH levels. These data, together with the observation that IL-6 production was increased in envenomed mice, suggests the presence of inflammation and muscle injury. Lungs histopathological analysis revealed the presence of diffuse hemorrhage due H. lunatus envenoming. It was observed that H. lunatus venom increased heart rate and causes various arrhythmias, thereby impairing the heart functioning. Calcium transient analysis was measured in isolated cardiomyocytes and appeared diminished, confirming that H. lunatus venom exerts a deleterious effect on heart. These data suggest that, despite having moderate toxicity to mammals, the H. lunatus venom is capable of inducing effects typical of scorpion envenoming, such as the cardio-pulmonary alterations demonstrated, and also presents less common activities observed in scorpion venoms, such as proteolytic and phospholipasic, justifying further studies of this venom.